Effect of Sublethal Doses of Imidacloprid on the Biological Performance of Aphid Endoparasitoid Aphidius gifuensis (Hymenoptera: Aphidiidae) and Influence on Its Related Gene Expression - Kang, Zhi-Wei; Liu, Fang-Hua; Pang, Rui-Ping; Tian, Hong-Gang; Liu, Tong-Xian (Frontiers in Physiology, 2018)
The integrated pest management (IPM) strategy was developed and used in combination with pesticides and beneficial biological control agents. To further develop IPM efficiency, it is important to evaluate the side effects of pesticides on biological control agents. Aphidius gifuensis is one of the most important aphid natural enemies and has been successfully used to control Myzys persicae and other aphid species. Imidacloprid (IMD) is a popular pesticide used worldwide and is highly toxic to non-target arthropods. Here, we investigated the short-term sublethal toxicity of IMD in Aphidius gifuensis and its impact on the biological performance and gene expression of this parasitoid. We found that sublethal IMD doses had a significant negative effect on the life history traits of female A. gifuensis, including shortening the lifespan and lowering parasitic capacity. Moreover, exposure to sublethal IMD also adversely affected the response of A. gifuensis to aphid-infested plant volatiles. Based on the transcriptome analysis, we found that the exposure to sublethal IMD doses significantly affected expression of genes involved in the central nervous system, energy metabolism, olfactory, and detoxification system of A. gifuensis. RT-qPCR also revealed that short term expose to sublethal IMD doses significantly induced the gene expression of genes related to the central nervous system (nAChRa7, nAChRa9, TbH, OAR1, NFR, TYR, and DAR1), olfactory system (OR28 and IR8a1), and detoxification system (CYP49p3, CYP6a2, and POD), while it suppressed the expression of genes involved in the central nervous system (nAChRa4 and nAChRb1), olfactory system (Orco1, IR8a2, and GR1), and detoxification system (GST2). Furthermore, exposure to sublethal doses of IMD also significantly increased the activities of CarEs and POD, whereas we observed no influence on the activities of CAT, GST, and SOD. Our results indicate that sublethal IMD doses might adversely affect the biological performance of A. gifuensis by altering gene expression related to the function of olfactory, nervous, energy metabolism, and detoxification systems. Thus, how the use of pesticides directly affect insect population should be considered when used in conjunction with natural pest parasitoids in IPM strategies.